Deep-seated pseudotachylytes from the Ivrea Zone metagabbros (Southern Alps, Italy) - Pittarello, L.; Pennacchioni, G.; Di Toro, G. (TRABAJOS DE GEOLOGÍA, 2010)
Pseudotachylytes associated with localized ultramlylonites occur in the Premosello granuliteamphibolitemetagabbros of the Ivrea Zone. Petrographic and microstructural data show that thepseudotachylyte developed under similar amphibolite facies metamorphic conditions as the ultramylonites.Our observations lend support to the model of several cycles of alternating pseudotachylytesand ultramylonites occurring in a dry middle-lower crust during the pre-Alpine exhumation. Thesepseudotachylytes might retain information on earthquake mechanics below the “normal” depth of thebrittle-plastic transition in the crust.